2014
DOI: 10.5897/ajmr2013.6138
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evaluation of Lactobacillus spp. for the development of potential probiotics

Abstract: Probiotics are live microbial food ingredients that have beneficial effects on consumption. The present study searched fermented food samples for potential lactobacilli that could be used for the development of novel gastrointestinal probiotics. Fifty five (55) isolates were obtained including 46 bacterial and 9 yeast isolates. On the basis of morphological and biochemical properties, 21 were identified as Lactobacillus spp. Systematic procedures were used to evaluate the probiotic properties of the Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The observed growth properties in the presence of pancreatin makes the adaptivity of the tested strains highly possible in these conditions. Khagwal et al [64] reported a resistance to the presence of pancreatin in a concentration of 0.5% for all tested LAB strains in their study. The growth dynamic in the presence of bile salts were assessed to evaluate the effect of different concentrations of bile salts on the studied strains (Figure 3).…”
Section: Growth Dynamics In the Presence Of Git Stress Factorsmentioning
confidence: 74%
See 1 more Smart Citation
“…The observed growth properties in the presence of pancreatin makes the adaptivity of the tested strains highly possible in these conditions. Khagwal et al [64] reported a resistance to the presence of pancreatin in a concentration of 0.5% for all tested LAB strains in their study. The growth dynamic in the presence of bile salts were assessed to evaluate the effect of different concentrations of bile salts on the studied strains (Figure 3).…”
Section: Growth Dynamics In the Presence Of Git Stress Factorsmentioning
confidence: 74%
“…The observed growth properties in the presence of pancreatin makes the adaptivity of the tested strains highly possible in these conditions. Khagwal et al [64] reported a resistance to the presence of pancreatin in a concentration of 0.5% for all tested LAB strains in their study.…”
Section: Autoaggregation and Mucin Binding Capabilitymentioning
confidence: 74%
“…The protein structure is the most pH-sensitive component in the cell. Moderate changes in pH modify the ionization of amino acid functional groups and disrupt hydrogen bonds, promoting changes in the molecule's folding, denaturation, and destroying activity [21].…”
Section: Discussionmentioning
confidence: 99%